(untitled) (Estudios Gerenciales, 2013)
Evidence on the relationship between wealth and happiness is mixed, hinting that there are situational or individual factors that account for the variability in results. This paper contends that wealth is in fact related to happiness. More specifically, it is proposed that poverty—as well as other adverse situations—has an undermining effect on happiness, and that this effect is attenuated by a collectivist orientation. Analyses of variance (ANOVAs) using data on happiness, wealth and culture from 197 countries, supplemented by a meta-analysis of empirical studies that explore the relationship between wealth and perceptions of happiness, support the hypothesized relationship between adversity and happiness, and the moderating effect that collectivism has on such relationship.